The Influence of an Acute Administration of Cannabidiol or Rivastigmine, Alone and in Combination, on Scopolamine-Provoked Memory Impairment in the Passive Avoidance Test in Mice - Marta Kruk-Slomka; Tomasz Slomka; Grazyna Biala (MDPI AG, 2024)
Memory is one of the most important abilities of our brain. The process of memory and learning is necessary for the proper existence of humans in the surrounding environment. However, sometimes there are unfavourable changes in the functioning of the brain and memory deficits occur, which may be associated with various diseases. Disturbances in the cholinergic system lead to abnormalities in memory functioning and are an essential part of clinical symptoms of many neurodegenerative diseases. However, their treatment is difficult and still unsatisfactory; thus, it is necessary to search for new drugs and their targets, being an alternative method of mono- or polypharmacotherapy. One of the possible strategies for the modulation of memory-related cognitive disorders is connected with the endocannabinoid system (ECS). The aim of the present study was to determine for the first time the effect of administration of natural cannabinoid compound (cannabidiol, CBD) and rivastigmine alone and in combination on the memory disorders connected with cholinergic dysfunctions in mice, provoked by using an antagonist of muscarinic cholinergic receptor-scopolamine. To assess and understand the memory-related effects in animals, we used the passive avoidance (PA) test, commonly used to examine the different stages of memory. An acute administration of CBD (1 mg/kg) or rivastigmine (0.5 mg/kg) significantly affected changes in scopolamine-induced disturbances in three different memory stages (acquisition, consolidation, and retrieval). Interestingly, co-administration of CBD (1 mg/kg) and rivastigmine (0.5 mg/kg) also attenuated memory impairment provoked by scopolamine (1 mg/kg) injection in the PA test in mice, but at a much greater extent than administered alone. The combination therapy of these two compounds, CBD and rivastigmine, appears to be more beneficial than substances administered alone in reducing scopolamine-induced cognitive impairment. This polytherapy seems to be favourable in the pharmacotherapy of various cognitive disorders, especially those in which cholinergic pathways are implicated.